A Case Study Off PC World Strategy Plan To Be Succed In Reaching 100 Outlets In Malaysia - Yong, Seet Siong (2008)
The objective of this thesis is to study PC World key success factors and strategies that can improve its competitive advantages. It wills also highlight the challenges facing in today's IT industry environment, in relation to technology , social , economics and political factors.